Controle híbrido de um robô autônomo seguidor de linha - Petry, Márcio Luís (2016)
This work describes the development of an autonomous line follower robot through the modeling and the implementation of a hybrid control system (part time continuous – part discrete state). We studied the PID classic controllers, the Fuzzy logic control for discrete-time systems, besides the system components and the electronics knowledge required to simulate and make a prototype. The prototype’s continuous controllers were mathematically modeled and implemented in a Matlab-based simulation tool. The control of discrete event systems was modeled with Moore’s automaton and it was simulated with Deslab and Supremica tools. Practical tests were made at testing tracks, which followed the RoboCore’s standards with the implementation of a hybrid control system in the prototype. Finally, we analyzed the differences between the Fuzzy and PID’s controllers, in which the PID controller showed better results.